The effectiveness of cyber resilience in protecting academic data of university institutions in Algeria - Mohamed yedou; Fatiha bara (Journal of Excellence for Economics and Management Research, 2026)
This study aims to explore the importance of having a digital environment characterized by cyber resilience in protecting academic data of university institutions published on websites, especially in light of increasing threats and security challenges such as hacking and cyber intrusions        To achieve the objectives of the study, the descriptive-analytical approach was adopted to address the issue. The finding syndicate that cyber resilience provides an integrated framework that includes formulating strategies in the field of cybersecurity to assess, detect early, and respond to cyber risks, as well as to recover operations in case of data breaches. It is also essential to develop policies and programs for research, development, and innovation in order to build a high level of security for IT infrastructures and networks that meet safety standards for protecting academic data in Algerian universities